Potencial alelopático de extratos de capim-arroz sobre germinação e crescimento de plantulas de espécie indicadora - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Allelopathy is the term used to define the interference one plant has over another through the release of chemical compounds into the surrounding environment, and such interference can be harmful or beneficial. Barnyard-grass is the most common weed in floodplain areas and is considered very competitive and responsible for major losses in grain yields when not satisfactorily controlled. In addition to competing with cultivated plants for resources in the environment, weeds can also interfere through allelopathy. For the initial investigation of allelopathic effects, an indicator species such as lettuce is generally used as a receptor. The aim of this work was to investigate the allelopathic effects of extracts produced from different parts of the barnyard-grass plant on the germination and initial growth of lettuce seedlings. The treatments used were different concentrations of barnyard-grass leaf and root extracts. Seed germination, aerial part and root system length and seedling fresh matter weight were assessed. The results were stimulatory and inhibitory, depending on the concentration used. The barnyard-grass leaf extract did not influence germination, only seedling growth. The length of the aerial part was stimulated by concentrations from 20 g/L, and the length of the root system from 40 g/L. All concentrations stimulated the accumulation of fresh matter mass in the seedlings. The barnyard-grass root extract inhibited seed germination and did not influence seedling growth. Germination was inhibited from a concentration of 10 g/L. It is therefore possible to state that the extracts of barnyard-grass leaves and roots produced allelopathic effects on the germination and initial growth of lettuce.
Allelopathic potential of barnyard grass extracts on germination and growth of indicator species seedlings
Keywords: Alelopatia; Aleloquímicos; Metabolismo secundário; Plantas daninhas; Allelopathy; Allelochemicals; Secondary metabolism; Weeds; CNPQ::CIENCIAS AGRARIAS